Patterns of paternal investment predict cross-cultural variation in jealous response - Scelza, Brooke A. (Nat Hum Behav, 2019)
Long-lasting, romantic partnerships are a universal feature of human societies, but almost as ubiquitous is the risk of instability when one partner strays. Jealous response to the threat of infidelity is well studied, but most empirical work on the topic has focused on a proposed sex difference in the type of jealousy (sexual or emotional) that men and women find most upsetting, rather than on how jealous response varies(1,2). This stems in part from the predominance of studies using student samples from industrialized populations, which represent a relatively homogenous group in terms of age, life history stage and social norms(3,4). To better understand variation in jealous response, we conducted a 2-part study in 11 populations (1,048 individuals). In line with previous work, we find a robust sex difference in the classic forced-choice jealousy task. However, we also show substantial variation in jealous response across populations. Using parental investment theory, we derived several predictions about what might trigger such variation. We find that greater paternal investment and lower frequency of extramarital sex are associated with more severe jealous response. Thus, partner jealousy appears to be a facultative response, reflective of the variable risks and costs of men’s investment across societies.